Harnessing generative AI for educational innovation: a TRIZ-PLR perspective - Muhammad Saqib Iqbal; Zulhasni Abdul Rahim; Qudrattullah Omerkhel (Discover Applied Sciences)
Abstract This study investigates the transformative potential of Generative Artificial Intelligence (GenAI) in education using the TRIZ-Patent Literature Review (TRIZ-PLR) framework. By analysing patents related to GenAI, this study identifies technological challenges, inventive solutions, and their implications for educational practices. The findings highlight advances in adaptive learning systems, optimised virtual classrooms, and predictive analytics, demonstrating how GenAI can improve personalised learning, student engagement, and academic performance. This study provides actionable information for educators, administrators, and technology developers, highlighting the importance of ethical considerations and equitable implementation. The study concludes with recommendations for scaling GenAI solutions in education, while addressing future research needs.